Pelaporan Keuangan Berbasis Komputer Di Takmir Masjid Mujahidin, Kecamatan Pademawu, Kabupaten Pamekasan: Pelaporan Keuangan Berbasis Komputer Di Takmir Masjid Mujahidin, Kecamatan Pademawu, Kabupaten Pamekasan - Nur Fathin Luaylik (Prapanca : Jurnal Abdimas, 2022)
Abstract Limited adninistration human resources in Mujahidin Mosque Takmir, Pamekasan Dstrict make consequences finance report used old technique. When more print the report and keep report physicly. Habitual more comfort use old system, make adminsitrators difficult using computer data storage . So that needs training make finance report computerized.The aim this community dedication give training teenager Mujahidin Mosque Takmir using computer set finishing the finance report, so that more organize within paperless. Community dedication method by training make finance report use computer aplication. After training held, todays Mujahidin Teenager Mosque Takmir are usual finishsed finance report computerized and have study more aplication to make easy job.The result community dedication conclude are used the manual reported, can subsituced with digital system by usuall and administartaor adapted, but more giving influence is develope of self motivation competence mainly using information technology. Keyword: Finance Report, Computer System, Mosque Takmir, Information technology